83.4k views
5 votes
The first step for deriving the quadratic formula from the quadratic equation, 0 = ax2 + bx + c, is shown. Step 1: –c = ax2 + bx Which best explains or justifies Step 1?

2 Answers

4 votes

Answer:

subtract c from each side, so the answer would be D

User Denizmveli
by
6.5k points
7 votes

Answer:

Subtract c from each side, using the subtraction property of equality

Explanation:

0 = ax^2 + bx + c

Subtract c from each side, using the subtraction property of equality

-c = ax^2 + bx + c-c

-c = ax^2 + bx

User Alexkb
by
6.3k points